MAA 161 - Statistics For Science Students November 2006 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2006)
UNIVERSITI SAINS MALAYSIA Kolej Legenda First Semester Examination Academic Session 2006/2007 October/November 2006 MAA 161 - Statistics For Science Students